Comparison of fatigue behavior in Mg/Mg similar and Mg/steel dissimilar refill friction stir spot welds. (November 2016) - Shen, Z.; Ding, Y.; Chen, J.; Gerlich, A.P.
Highlights: The Zn coating is beneficial to bond formation between Mg/steel sheets. The Zn coating also contributes to brazing outside the weld boundary. Mg/steel weld exhibit superior static and fatigue behavior compared to Mg/Mg welds. Abstract: Mg/Mg similar and Mg/steel dissimilar spot welds were produced using refill friction stir spot welding. For comparison, the Mg/Mg and Mg/steel welds were evaluated in terms of microstructures, microchemical analysis, interfacial reactions, tensile-shear and fatigue fracture. Acceptable Mg/steel dissimilar spot weld strength can be obtained by plunging the sleeve to a depth 0.05 mm above the Mg/steel interface. The presence of a 10 μm zinc coating on the DP600 steel surface is beneficial to the bond formation between Mg/steel sheets, which also contributes to brazing outside the weld boundary. Hence, this increases the bonded area for Mg/steel welds compared to Mg/Mg spot welds. Consequently, Mg/steel dissimilar welds exhibit superior overlap shear static and fatigue behavior compared to Mg/Mg similar spot welds. When stress P max ⩽ 1450 N, all of the welds fractured at the Mg parent sheet. Most fatigue fractures in Mg/steel welds occurred at the sheet interface, however when 1087 N ⩽ P max ⩽ 1812 N, Mg/steel welds occasionally fractured through the Mg parent sheet. When the fatigue fracture propagation occurred through the parent Mg sheet in Mg/steel welds, superior fatigue behavior is observed and attributed to zinc brazing at the surrounding weld interface. The SEM and fracture analysis show that fatigue cracks at the parent Mg sheet initiated from multiple sites located at the Mg side and then propagated into the base material.